Cultural Awareness and Government Support as Determinants of Tourism Village Sustainability: Evidence from Bali - Sazali, Hasan; Matondang, Abdul Rahman; Zuhriah, Zuhriah; Hadipramana, Josef (Jurnal Ilmiah Peuradeun, 2025)
This study examines the impact of cultural awareness on the sustainability of tourist villages in Bali, with government support and communication patterns as moderating variables. The research employs a quantitative approach, utilizing Smart PLS for data analysis, with a sample of 100 respondents from tourist villages in Bali, a region known for its rich cultural diversity and environmental challenges from mass tourism. The findings indicate that cultural awareness significantly influences the sustainability of tourist villages (T statistic = 9.563, p-value = 0.000), while government support has a marginally significant effect (T statistic = 1.893, p-value = 0.059). However, communication patterns do not show a significant impact (T statistic = 0.355, p-value = 0.723). Moderated Regression Analysis (MRA) reveals that government support strengthens the relationship between cultural awareness and sustainability, whereas communication patterns do not significantly alter this effect. These results suggest that while cultural awareness is a key determinant of sustainability, government support plays a critical moderating role, emphasizing the need for stronger policy interventions to enhance sustainable tourism development in Bali’s tourist villages.